2018
DOI: 10.5603/arm.2018.0034
|View full text |Cite
|
Sign up to set email alerts
|

The Concurrence of Granulomatous Inflammation in Intrathoracic Lymph Nodes with Regional Metastasis from Primary Lung Cancer in Surgically Resected Specimens

Abstract: Introduction: Granulomatous inflammation has been associated with malignancies such as breast, testicular, renal cell, and lymphoma. The coexistence of granulomatous inflammation in mediastinal/hilar lymph node with primary lung malignancy has been described in case reports. Our goal was to examine the frequency of granulomatous reaction in mediastinal/hilar lymph node in the patients who had undergone surgical resection of lung cancer. Material and methods: We performed a retrospective analysis of 40 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In our study infectious disease was found in 16 patients, most of them due to tuberculous infection. At the same time, as other authors have also reported, potentially fatal diseases such as a malignancy can also occur [18][19][20]. In the present series, neoplasms were detected in 12 patients.…”
Section: Characteristic (N=207)supporting
confidence: 82%
“…In our study infectious disease was found in 16 patients, most of them due to tuberculous infection. At the same time, as other authors have also reported, potentially fatal diseases such as a malignancy can also occur [18][19][20]. In the present series, neoplasms were detected in 12 patients.…”
Section: Characteristic (N=207)supporting
confidence: 82%